Honour and shame in Psalm 44 - Mare, Leonard P. (Scriptura : Journal for Contextual Hermeneutics in Southern Africa, 2014)
Honour and shame were core social values of the ancient Mediterranean world. Nearly everything pertaining to relationships was determined by these two concepts. Honour was the goal, passion and hope of everyone wishing to succeed in life. Being shamed was a social catastrophe. Honour was thus understood as the direct contrast of shame, specifically negative shame, because positive shame, usually ascribed to females, was understood to be a virtue. Honour and shame took a central place in relationships between humans, but also in the relationship between God and human. These concepts of honour and shame play a central role in Psalm 44. The first stanza with the joyful exuberance of Israel remembering and celebrating God's glorious deeds on their behalf, serves as an expression of Israel's honour, and the other nations' shame. In the lament of stanza 2 God is blamed for the people's suffering. God has rejected and humbled them; they are disgraced and shamed. God's rejection is experienced in various ways; the end result is that Israel is covered with disgrace and shame. In the third stanza the plea of innocence is an expression of their conviction that they don't deserve their position of shame, and that they should be restored to a position of honour. In stanza 4 the people petition God to act on their behalf again and thus change their shame into honour.
free